Exploration of Fabric Applique Techniques in Designing Art of Beat Style Fashion - Nur Tasya; Dini Yanuarmi; Mirda Aryadi; Fadri Rahmat (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Art of beat style fashion is an art from that demonstrates freedom of expression, creativity, and a unique artistic flair. This style emerged as a rejection of mainstream aesthetics by showcasing a distinctive, artistic, and individual visual character. One of the techniques used in this fashion is fabric applique, which can create decorative, complex, and artistic surface designs. The method of creation is carried out through exploration, design, embodiment, and presentation. The exploration stage involves gathering references and developing the art of beat style concept. The design stage includes sketching, color selection, and material selection, as well as experimenting with fabric applique techniques combined with thread applique, thread embroidery, sashiko, and ruffle. The implementation stage involves pattern making, cutting the material, applying decorative techniques, and finishing the garment. The creations are presented in three levels of fashion: ready to wear entitled neon reverie, ready to wear deluxe entitled chaos in color, and haute couture entitled spectrum renjana. The three works utilize bright, contrasting colors such as red, yellow, purple, and pink. The works are presented throught a fashion show with an artistic concept that supports the eccentric and expressive character of the garments. Through this presentation, the art of beat style character and application of fabric draping techniques are maximally displayed, resulting in unique, innovation works with a strong visual identity Keywords: Art of beat style, fabric embroidery, rope embroidery, embroidery, aesthetics   Abstrak Busana art of beat style adalah bentuk seni yang menunjukkan kebebasan dalam berpenampilan, kreativitas, serta nuansa artistik dan unik. Gaya ini tumbuh sebagai bentuk penolakan terhadap estetika yang umum dengan menunjukkan karakter visual yang khas, artistik, dan individual. Salah satu teknik yang dipakai  dalam busana ini adalah teknik lekapan kain yang mampu menciptakan desain permukaan yang dekoratif, kompleks, dan bernilai seni. Metode penciptaan dilakukan melalui eksplorasi, perancangan, perwujudan, dan penyajian. Tahap eksplorasi dilakukan melalui pengumpulan referensi dan pengembangan konsep art of beat style. Tahap perancangan meliputi pembuatan sketsa, pemilihan warna, material, serta eksperimen teknik lekapan kain yang dipadukan dengan teknik lekapan benang, sulam benang, sashiko, dan ruffle. Tahap perwujudan dilakukan melalui proses pembuatan pola, pemotongan bahan, penerapan tenik hias, hingga penyelesaian busana. Hasil penciptaan diwujudkan dalam tiga tingkatan busana yaitu ready to wear dengan judul karya “neon reverie”, ready to wear deluxe dengan judul “chaos in color”, dan haute couture dengan judul “spectrum renjana”. Ketiga karya mengaplikasikan warna-warna cerah dan kontras seperti merah, kuning, ungu, dan pink.. Karya disajikan melalui pergelaran busana (fashion show) dengan konsep artistik yang mendukung karakter eksentrik dan ekspresif dari busana. Melalui penyajian tersebut, karakter Art of Beat Style dan penerapan teknik lekapan kain dapat ditampilkan secara maksimal sehingga menghasilkan karya unik, inovatif, dan memiliki identitas visual yang kuat. Kata Kunci: Art of beat style, lekapan kain, lekapan benang, sulam, estetika